Anti-Obesity Effects of Adzuki Bean Saponins in Improving Lipid Metabolism Through Reducing Oxidative Stress and Alleviating Mitochondrial Abnormality by Activating the PI3K/Akt/GSK3β/β-Catenin Signaling Pathway - Jinhai Luo; Jincan Luo; Yingzi Wu; Yu Fu; Zhonghao Fang; Bincheng Han; Bin Du; Zifeng Yang; Baojun Xu (MDPI AG, 2024)
Obesity is a chronic and complex disease defined by the excessive deposition of fat and is highly associated with oxidative stress. Adzuki bean saponins (ABS) showed anti-obesity activity in our previous in vivo study; however, the active saponins of adzuki beans and potential mechanisms are still unclear. This research aims to elucidate the anti-obesity effects of ABS in improving lipid metabolism and oxidative stress, exploring the effective ingredients and potential molecular mechanisms through UHPLC-QE-MS analysis, network pharmacology, bioinformatics, and in vitro experiments both in the 3T3-L1 cell line and HepG2 cell line. The results indicate that ABS can improve intracellular lipid accumulation, adipogenesis, oxidative stress, and mitochondrial damage caused by lipid accumulation including ROS generation, abnormal mitochondrial membrane potential, and ATP disorder. Fifteen saponin components were identified with the UHPLC-QE-MS analysis. The network pharmacology and bioinformatics analyses indicated that the PI3K/Akt signaling pathway is associated with the bioactive effect of ABS. Through Western blotting and immunofluorescence analysis, the anti-obesity effect of ABS is achieved through regulation of the PI3K/Akt/GSK3β/β-catenin signaling pathway and activation of downstream transcription factor c-Myc in the lipid accumulation cell model, and regulation of β-catenin signaling and inhibition of downstream transcription factor C/EBPα in the adipocyte cell model. These results illustrate the biological activity of ABS in improving fat metabolism and oxidative stress by restoring mitochondrial function through β-catenin signaling, the PI3K/Akt/GSK3β/β-catenin signaling pathway, laying the foundation for its further development.